Experimental and Numerical Investigation to Enhance the Performance of Helical Coiled Tube Heat Exchanger by Using Turbulators - Saleh Mahdi, Qasim; Abdul Fattah , Sahar; Mahdi Jasim , Osama (Journal of Engineering and Sustainable Development, 2014)
In the present work, a numerical and experimental investigation is carried out to evaluate the performance of a helically coiled tube heat exchanger with a wire coil insert. Experimental work included the design of wire coiled and inserted into a vertically positioned plain copper helical tube heat exchanger. The effects of wire coil insert with different parameters on heat transfer and friction loss in the helical tube were examined with Dean numbers ranging from 700 to 2000. The experiments of coiled wire were performed, firstly with three different pitches (P= 15, 20, and 30)mm with a constant circular cross-section(a=1mm), secondly with a different cross-section (circular and square) at a constant pitch of 15mm, and thirdly with two different square wire thickness (a =1, 2) mm at constant pitch 15mm. The numerical analysis was carried out to simulate the flow and heat transfer in a helical coil tube with a wire coil insert at pitch (15mm) with different flow rates by using ANSYS FLUENT package 14.0. The experimental results showed that the use of tubular leads to a considerable increase in heat transfer and friction loss over those of a smooth coiled tube. The Nusselt number increases with the increasing of Dean number and the reduction in pitch for wire coils. The coiled square wire provides higher heat transfer than the circular one under the same conditions. New empirical correlations have been developed to predict the Nusselt number of the helical coil heat exchanger...